Engineering the alternative oxidase gene to better understand and counteract mitochondrial defects: state of the art and perspectives. (April 2014) - El‐Khoury, Riyad; Kemppainen, Kia K; Dufour, Eric; Szibor, Marten; Jacobs, Howard T; Rustin, Pierre
<x xml:space="preserve">Abstract</x> Mitochondrial disorders are nowadays recognized as impinging on most areas of medicine. They include specific and widespread organ involvement, including both tissue degeneration and tumour formation. Despite the spectacular progresses made in the identification of their underlying molecular basis, effective therapy remains a distant goal. Our still rudimentary understanding of the pathophysiological mechanisms by which these diseases arise constitutes an obstacle to developing any rational treatments. In this context, the idea of using a heterologous gene, encoding a supplemental oxidase otherwise absent from mammals, potentially bypassing the defective portion of the respiratory chain, was proposed more than 10 years ago. The recent progress made in the expression of the alternative oxidase in a wide range of biological systems and disease conditions reveals great potential benefit, considering the broad impact of mitochondrial diseases. This review addresses the state of the art and the perspectives that can be now envisaged by using this strategy. Linked Articles This article is part of a themed issue on Mitochondrial Pharmacology: Energy, Injury & Beyond. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2014.171.issue‐8